2005
DOI: 10.1111/j.1365-2893.2005.00562.x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the relative levels of wild‐type and lamivudine‐resistant mutant virus in serum of HBV‐infected patients using microarray

Abstract: During the course of lamivudine administration in hepatitis B virus (HBV)-infected patients, a dynamic development of the viral population in serum is observed. Total HBV level is initially reduced, then lamivudine-resistant mutants appear, and finally, the viral level is increased. All methods of mutant detection so far described can only identify mutants in the serum, and cannot determine the proportion of those mutants. In this paper, we report the development of a novel technique that can quantify the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 9 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…Other genotyping methods that are still being developed rely on hybridization coupled to a variety of detection techniques including mass spectrometry [63,64], computer assisted microarray analysis [65][66][67], luciferase assays [68], or electrochemical methods based on oxidation of guanine [69]. All are rapid and accurate but require expensive equipment and highly trained personnel.…”
Section: Genotypingmentioning
confidence: 99%
“…Other genotyping methods that are still being developed rely on hybridization coupled to a variety of detection techniques including mass spectrometry [63,64], computer assisted microarray analysis [65][66][67], luciferase assays [68], or electrochemical methods based on oxidation of guanine [69]. All are rapid and accurate but require expensive equipment and highly trained personnel.…”
Section: Genotypingmentioning
confidence: 99%
“…In addition, this technique does not allow a mutation frequency estimate, so it is not suitable for dynamic studies. Other sequence-specific genotypic resistance tests are available or are being developed, such as restriction fragment length/mass polymorphism (11,33,41), oligonucleotide microarray and gene chip technology (19,36), mutation-specific real-time PCR (39), matrix-assisted laser desorption ionization-time of flight mass spectrometry (17), and pyrosequencing (14,20). On the whole, all of the sequence-specific methods present the same drawbacks of reverse hybridization.…”
mentioning
confidence: 99%
“…Previous reports indicated that during the course of LMV therapy, HBV DNA in patient serum often reduces to an undetectable level -a situation which lasted for a long time and then reversed to the pre-treatment level (Li et al, 2005;Pallier et al, 2006). During this process, resistant variants were generated which finally replaced all WT YMDD strains and then the pathological effects appeared.…”
Section: Discussionmentioning
confidence: 99%